2021
DOI: 10.3389/fonc.2021.659676
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Heterogeneous Nuclear Ribonucleoprotein C Inhibit Hepatocellular Carcinoma Proliferation, Migration, and Invasion via Ras/MAPK Signaling Pathway

Abstract: Hepatocellular carcinoma (HCC), the most common malignant tumor, has high fatality and recurrence rates. Accumulating evidence shows that heterogeneous nuclear ribonucleoprotein C (HNRNPC), which is mainly involved in RNA splicing, export, and translation, promotes progression and metastasis of multiple tumor types; however, the effects of HNRNPC in HCC are unknown. In the present study, high levels of HNRNPC were detected in tumor tissues compared with para-tumor tissues by immunohistochemical and western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…We next focused on the interaction of the hsa_circ_0062682 with proteins previously implicated in the pathology of HCC, namely YBX1 (Y-box-binding protein 1) [ 48 ], IGF2BP1 (Insulin-like growth factor 2 mRNA-binding protein 1) [ 49 ], hnRNP C1/C2 (Heterogeneous nuclear ribonucleoproteins C1/C2) [ 50 ], hnRNP K (Heterogeneous nuclear ribonucleoprotein K) [ 51 ], CSNK2A1 (Casein kinase II subunit alpha) [ 52 ], and ENO1 (Alpha-enolase) [ 53 ]. While YBX1, IGF2BP1, hnRNP C1/C2, and hnRNP K are known to bind RNAs and have roles in RNA metabolism, it has also been shown for CSNK2A1 and ENO1 to be able to bind RNA molecules [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…We next focused on the interaction of the hsa_circ_0062682 with proteins previously implicated in the pathology of HCC, namely YBX1 (Y-box-binding protein 1) [ 48 ], IGF2BP1 (Insulin-like growth factor 2 mRNA-binding protein 1) [ 49 ], hnRNP C1/C2 (Heterogeneous nuclear ribonucleoproteins C1/C2) [ 50 ], hnRNP K (Heterogeneous nuclear ribonucleoprotein K) [ 51 ], CSNK2A1 (Casein kinase II subunit alpha) [ 52 ], and ENO1 (Alpha-enolase) [ 53 ]. While YBX1, IGF2BP1, hnRNP C1/C2, and hnRNP K are known to bind RNAs and have roles in RNA metabolism, it has also been shown for CSNK2A1 and ENO1 to be able to bind RNA molecules [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…HNRNPA2B1 binds directly to the PFN2 mRNA at the site of the UAGGG sequence of the 3′-UTR and reduces its stability ( Liu et al, 2020b ). Specifically, another report has indicated that decreased HNRNPC expression reduces the activation of the Ras/MAPK signaling pathway ( Hu et al, 2021 ) ( Figure 2 and Table 3 ).…”
Section: The Signaling Pathway Involved In M 6 a R...mentioning
confidence: 97%
“…MAPK signaling cascade, with the Ras-Raf-MEK-MAPK signaling pathway, is involved in various cellular and physiological processes essential to life (46). When extracellular stimulators bind to transmembrane receptors, inactive Ras-GDP in the plasma membrane is converted to active Ras-GTP, which then stimulates active homodimerization consisting of A-Raf, B-Raf, and C-Raf formation of dimeric or heterodimers.…”
Section: Effects On Tumor Proliferation and Metastasismentioning
confidence: 99%